2009
DOI: 10.1002/chin.200908160
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Asymmetric Intramolecular Oxa‐Michael Addition of Activated α,β‐Unsaturated Ketones Catalyzed by a Chiral N,N′‐Dioxide Nickel(II) Complex: Highly Enantioselective Synthesis of Flavanones.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Since the first example of catalytic asymmetric intermolecular oxa-Michael addition was disclosed by the Jacobsen group using (salen)aluminum catalysts in 2004, 347 workers described an asymmetric intramolecular oxa-Michael addition of the phenol group to activated enones catalyzed by chiral complexes L20d−Ni(II) (Scheme 86a), 85 generating the corresponding enantiopure flavanones in 90−99% yields and 80−99% ee's. Later studies showed that the chiral N,N′dioxide−iron(II) complexes (L21e−Fe) could be successfully applied to the intermolecular oxa-Michael addition of oximes to α,β-unsaturated aldehydes, which led to the corresponding adducts in moderate to good yield with up to 76% ee (Scheme 86b).…”
Section: Conjugate Addition Of Oxygen Nucleophilesmentioning
confidence: 99%
“…Since the first example of catalytic asymmetric intermolecular oxa-Michael addition was disclosed by the Jacobsen group using (salen)aluminum catalysts in 2004, 347 workers described an asymmetric intramolecular oxa-Michael addition of the phenol group to activated enones catalyzed by chiral complexes L20d−Ni(II) (Scheme 86a), 85 generating the corresponding enantiopure flavanones in 90−99% yields and 80−99% ee's. Later studies showed that the chiral N,N′dioxide−iron(II) complexes (L21e−Fe) could be successfully applied to the intermolecular oxa-Michael addition of oximes to α,β-unsaturated aldehydes, which led to the corresponding adducts in moderate to good yield with up to 76% ee (Scheme 86b).…”
Section: Conjugate Addition Of Oxygen Nucleophilesmentioning
confidence: 99%
“…This stereocenter in the abyssinones is quite sensitivemildly basic conditions promote reversible ring-opening to achiral 2′-hydroxychalcones . In addition, flavanones containing electron-donating substituents in the C4′ position are particularly susceptible to racemization. , A limited number of approaches for the stereoselective synthesis of flavanones have been developed, but these approaches are not general and would not provide the abyssinone core in a concise manner. …”
mentioning
confidence: 99%
“…Our synthetic plan is outlined in Figure . The key step in the strategy is the application of our asymmetric thiourea-catalyzed cyclization, which can provide controlled access to either stereoisomer of these natural products. , A Knoevenagel condensation between an appropriately protected β-keto ester and different aldehydes corresponding to each abyssinone would provide the requisite alkylidenes for our thiourea-catalyzed cyclization. Our greatest concern was maintaining the integrity of the newly formed C2 stereocenter, which would depend heavily on the identification of mild decarboxylation/deprotection conditions.…”
mentioning
confidence: 99%
“…The chiral nickel(II) N,N′-dioxide complex (2S,3aS,6aS)-XVIIb belongs to a catalyst family already encountered in previous sections and gives a "one-pot" [oxa-Michael/decarboxylation] reaction, affording (R)-671 with broad substrate scope since the chiral flavanones are obtained with excellent yields and very good enantioselectivities over 15 experiments (Scheme 275). 324 Worse results are obtained with chiral N-triflylphosphoramide (S)-CL because both the oxa-Michael products (2S,3R)-672 and the products of the "one-pot" [oxa-Michael/decarboxylation] reaction, (S)-671, are obtained with good yields, but unsatisfactory enantioselectivities (Scheme 275). 325 The intramolecular oxa-Michael cyclization was also applied to different classes of reagents.…”
Section: Formation Of the O(1)−c(2) Bondmentioning
confidence: 99%
“…Scheme 275. Enantioselective Intramolecular [Oxa-Michael Cyclization/Decarboxylation] of (E)-668 with Different Catalysts324,325 …”
mentioning
confidence: 99%